2009
DOI: 10.1158/0008-5472.can-08-2610
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C Is a Novel RBPJκ-Induced Target Gene for Notch Signaling in Gliomas

Abstract: Tenascin-C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
111
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 51 publications
11
111
0
Order By: Relevance
“…Tenascin-C is strongly implicated in mediating the invasive behavior of glioma cells, and early studies showed that tenascin-C stimulated fibronectinmediated cell migration (Deryugina and Bourdon 1996). Similar observations have been made by several different research groups (Hirata et al 2009;Sivasankaran et al 2009); in one report, this migration was found to be dependent on the induction of metalloproteinase-12 (Sarkar et al 2006). The connection between tenascin-C expression and invasion is, however, not restricted to brain tumors.…”
Section: Tenascins In Cell Migration Cancer Cell Invasion and Metassupporting
confidence: 82%
See 1 more Smart Citation
“…Tenascin-C is strongly implicated in mediating the invasive behavior of glioma cells, and early studies showed that tenascin-C stimulated fibronectinmediated cell migration (Deryugina and Bourdon 1996). Similar observations have been made by several different research groups (Hirata et al 2009;Sivasankaran et al 2009); in one report, this migration was found to be dependent on the induction of metalloproteinase-12 (Sarkar et al 2006). The connection between tenascin-C expression and invasion is, however, not restricted to brain tumors.…”
Section: Tenascins In Cell Migration Cancer Cell Invasion and Metassupporting
confidence: 82%
“…Examples of breast and colon carcinomas are shown in Figure 4. In other cancers such as melanoma or glioblastoma, the cancer cells themselves are secreting tenascin-C (Natali et al 1990;Herlyn et al 1991;Sivasankaran et al 2009) and both tenascin-C as well as tenascin-W are present in brain cancer blood vessels (Higuchi et al 1993;Zagzag et al 1995;Kim et al 2000;Martina et al 2009). Tenascin-W staining correlates with von Willebrand factor staining, which is consistent with tenascin-W production by endothelial cells (Fig.…”
Section: Tenascins In Cell Migration Cancer Cell Invasion and Metasmentioning
confidence: 99%
“…Thus, TNC + /Oct-4 + cells grew as neurospheres in vitro for many passages, a feature typical of tumor stem/progenitor cells [35,68]. These neurospheres expressed stem cell-related markers such as βIII-tubulin, HIF-2α, nestin and Notch-2, which controls TNC expression and angiogenesis [69]. Three lines of evidence demonstrated unambiguously that TNC + /Oct-4 + cells were the progenitors of NBderived ECs, and namely (i) in vitro these cells, but not their TNC − counterparts, differentiated into endotheliallike cells expressing VE-cadherin, PSMA and to a lesser extent CD31 after culture with VEGF, and (ii) in vivo TNC + , but not TNC − HTLA-230 cells, formed ortothopic tumors in which a half of the EMs were lined by NB-derived ECs.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it was decided to examine the in vitro effects of these chroman-type potassium-channel openers and related structures on the growth of three human highgrade glioma cell lines, i.e. U373 and T98G from astroglial origin [25e27] and Hs683 from oligodendroglial origin [25,26,28]. While the Hs683 model displays actual sensitivity to pro-apoptotic stimuli [25,29], the U373 [25,29] and T98G [29] models do not.…”
Section: Introductionmentioning
confidence: 99%